Perceptions of academic workload with particular reference to research : a cross sectional survey of lecturing staff at the Port Elizabeth Technikon - Ruscheniko, Iona Helen Felicity (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2001.